DETERMINANTS OF ACCOUNTING STUDENTS’ INTEREST IN BECOMING TAX CONSULTANTS - Ni Kadek Bintang Adi Agustini; Ni Luh Supadmi (CV. Adiba Aisha Amira, 2026)
The low level of interest among accounting students in pursuing a career as tax consultants has become an important issue amid the increasing demand for professional expertise in taxation. This study aims to empirically examine the effects of taxation knowledge, self-efficacy, perception, and work environment on accounting students’ interest in becoming tax consultants. This study employed a quantitative approach with an associative research design and was conducted at the Undergraduate Accounting Study Program, Faculty of Economics and Business, Udayana University. Primary data were collected through questionnaires distributed to 120 students selected using purposive sampling techniques. Data were analyzed using multiple linear regression analysis. The results indicate that taxation knowledge, self-efficacy, perception, and work environment have positive and significant effects on accounting students’ interest in becoming tax consultants. These findings suggest that higher levels of taxation knowledge and self-efficacy, more positive perceptions of the profession, and more conducive perceived work environments are associated with stronger interest among accounting students in pursuing a career as tax consultants. Theoretically, this study reinforces the Theory of Planned Behavior. Practically, the findings provide recommendations for study programs to strengthen practice-based taxation curricula, optimize elective courses in taxation, and facilitate students interested in becoming tax consultants in obtaining tax consultant certifications (tax brevet) through collaboration with training institutions and mentoring programs, thereby enabling students to prepare themselves more comprehensively.